2009
DOI: 10.1007/s10661-009-1038-y
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of different microorganisms with nickel and cadmium in the industrial wastewater and agricultural soils

Abstract: Wastewater and soil samples were collected from the industrial area of Ghaziabad City, India from January 2005 to December 2007 and were analyzed for the presence of heavy metals by atomic absorption spectrophotometry. Test samples revealed high levels of Fe, Cr, Cu, Ni, Zn, and Cd as 967.03, 34.63, 27.97, 19.7, 16.70, and 3.20 mg/L of wastewater, respectively. The concentrations of inorganic minerals were higher in the soil samples irrigated with wastewater. Total coliforms were found to be maximum (1,133x10(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…Common letter (s) over the error bars do not significantly differ (p < 0.05) according to DMRT to polluted habitats (Sivakumar et al 2012). Heavy metals are known inhibitors of microbial growth and soil enzyme activity (Kizilkaya and Bayrakli 2005;Ying et al 2008;Lee et al 2009;Ansari and Malik 2010;Rehman and Anjum 2011). The activities of soil enzymes have also been correlated with certain soil properties, such as temperature, moisture content, nutritional status, organic matter content and pH (Salam et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Common letter (s) over the error bars do not significantly differ (p < 0.05) according to DMRT to polluted habitats (Sivakumar et al 2012). Heavy metals are known inhibitors of microbial growth and soil enzyme activity (Kizilkaya and Bayrakli 2005;Ying et al 2008;Lee et al 2009;Ansari and Malik 2010;Rehman and Anjum 2011). The activities of soil enzymes have also been correlated with certain soil properties, such as temperature, moisture content, nutritional status, organic matter content and pH (Salam et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Niemeyer et al [10] reported a negative correlation between total Ni and Cr as well as other heavy metals (Fe, Cu, Mn, Zn, Cd, Pb) and ammonifiers. Previous findings in experimental conditions indicate that asymbiotic N 2 fixers are the most affected microbial group with an increasing concentration of Ni [33]. In addition, adding Ni to soil caused a 60% decrease in the number of oligotrophic bacteria and inhibits nitrification processes by up to 20% in comparison to clean soils [34].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, adding Ni to soil caused a 60% decrease in the number of oligotrophic bacteria and inhibits nitrification processes by up to 20% in comparison to clean soils [34]. It seems that the microorganisms included in the nitrogen metabolism in the soil (ammonifiers and oligonitrofiles) are among the more sensitive to the heavy metal pollution/concentrations [27,33].…”
Section: Discussionmentioning
confidence: 99%
“…Soils also play an important role for the global flux for pesticides in the environment (Sanghi and Sasi, 2001;Ansari and Malik, 2010). They are very important in the fate and distribution of persistent toxic substances in the environment since they have a huge retention capacity and they may work as re-emission sources for the atmosphere (Harner et al 2001;Barra et al, 2005;Ansari and Malik, 2010). Heavy metals are dangerous because they tend to bioaccumulate in living things any time they are taken up and stored faster than they are broken down (metabolized) or excreted (Mashi and Alhassan, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The soil is a long-term sink for the group of potentially toxic elements often referred to as heavy metals like zinc, copper, nickel, lead, chromium, and cadmium. While these elements display a range of properties in agricultural soil, including differences in mobility and bioavailability, leaching losses and plant uptake are usually relatively small compared to the total quantities entering the soil from different diffuse and agricultural sources (Ansari and Malik, 2010). Metals such as lead, mercury, cadmium and copper are cumulative poisons.…”
Section: Introductionmentioning
confidence: 99%